Diagnostics of plasma of electric arc discharge between asymmetric single-component Cu and Ni electrodes - Murmantsev, A.; Veklich, A.; Boretskij, V.; Fesenko, S.; Kleshych, M. (Problems of Atomic Science and Technology, 2023)
In this work, the radial distributions of parameters of plasma with copper and nickel vapours admixtures in positive column of electric arc discharge were investigated by optical emission spectroscopy. The plasma temperature was determined by the Boltzmann plot technique on the basis of absolute values of radiation intensity of both copper and nickel atomic spectral lines. Concentrations of both kinds of metal atoms of electrode origin were determined by the method of absolute intensities of the corresponding spectral lines of radiation of such plasma. Методами оптичної емісійної спектроскопії досліджено радіальні розподіли параметрів плазми з домішками парів міді та нікелю в позитивному стовпі дугового розряду. Температура плазми визначалась методом діаграм Больцмана із залученням абсолютних значень інтенсивності випромінювання спектральних ліній як атомів міді, так і нікелю. Концентрації обох сортів атомів металів електродного походження визначались методом абсолютних інтенсивностей відповідних спектральних ліній випромінювання такої плазми.